Joint forest Management - some Fundamentals Reviewed - Sharma, Jitendra (Indian Forester, 1997)
This paper looks at ecological and social objectives that could be achieved through implementation of JFM programmes. It also examines the likelihood of changing needs and responses of the local communities in different types of possible socio-economic scenarios in which participative forestry programmes will have to operate in future. Need for research in various important policy related areas for JFM programmes as well as areas of potential conflict are also highlighted.